2020
DOI: 10.1096/fj.201903035r
|View full text |Cite
|
Sign up to set email alerts
|

Generation of myostatin‐knockout chickens mediated by D10A‐Cas9 nickase

Abstract: Many studies have been conducted to improve economically important livestock traits such as feed efficiency and muscle growth. Genome editing technologies represent a major advancement for both basic research and agronomic biotechnology development. The clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 technical platform is a powerful tool used to engineer specific targeted loci. However, the potential occurrence of off‐target effects, including the cleavage of unintended targets, limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 33 publications
0
98
0
2
Order By: Relevance
“…Interestingly, we found that myostatin (MSTN) was also one of top 20 down-regulated genes. MSTN, a member of transforming growth factor beta (TGFbeta) superfamily, has been reported as a negative regulator of muscle growth and development [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that myostatin (MSTN) was also one of top 20 down-regulated genes. MSTN, a member of transforming growth factor beta (TGFbeta) superfamily, has been reported as a negative regulator of muscle growth and development [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date have examined the gain and loss‐of‐function of MSTN in chicken embryos, the consequences for the muscle progenitor population, and the association between MSTN SNPs and broiler performance 39,40 . We did not further analyze the our MSTN genome‐modified chickens in detail, but recent studies showed that mutation of MSTN in chicken 41 and quail has an anti‐myogenic effect 42 ; moreover, spatial MSTN mutations introduced by adenoviral CRISPR‐Cas9 induce differential gene expression involved in cell differentiation, muscle growth and development, and energy metabolism in postnatal chicken 43 . Therefore, we expect that these animals will exhibit elevated protein synthesis capacity as well as improved muscle cell development.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the myostatin (MSTN) gene gains huge attention, because MSTN is a negative regulator of muscle growth, and mutation in the MSTN gene resulted in increased muscle mass in mammals and fishes [92][93][94][95][96][97][98][99][100][101][102]. To investigate anti-myogenic function of MSTN in the avian species, MSTN knockout quail and chickens were generated by using the adenovirus-and PGC-mediated method, respectively [72,87]. Significant increase in breast and leg muscle in both MSTN knockout quail and chicken indicated that MSTN can be a potential selection marker for poultry lines with higher meat yield.…”
Section: Industrial Purposementioning
confidence: 99%